Enhancement of Kansei engineering methodology for sound design - Yiap, Shin Yi (2017)
Kansei Engineering (KE) is a method used to measure human feelings and emotions, and then relate these to certain product properties. Applied into many products such as automobiles, households' items and websites, this method has proven effective in linking human perceptions and design parameters to create products that address intended feelings and emotions. This method however is yet to be applied into the context of sound design notwithstanding that psychological concepts linked to feelings and emotions could be evoked by sound. A listener's main reaction would be to interpret the sound he hears with this perception and interpretation influenced by feelings and emotions. Current design processes of sound applications do not take into consideration users' feelings and emotions. This research therefore offers an investigation into embedding the right and intended feelings and emotions into sound by using the Kansei Engineering approach. By applying the Kansei Engineering approach into sound design, the physical properties of sound with selected Kansei words were examined, to establish an atmosphere whereby the user's intended feelings and emotions could be ascertained. An enhancement of the Kansei Engineering framework is thereafter presented to link Kansei and sound physical properties. The experiment used the quantitative research approach with four types of sound samples utilised to verify and support the framework. The experiment was conducted in four phases whereby users' feelings and emotions towards the physical properties of sound were generated at the end of synthesis phase. Four types of sound physical properties were chosen to induce certain feelings and emotions in users towards the sound samples. Data was obtained through in-depth questionnaires with the results used to support the idea of implementing the Kansei Engineering approach to improve sound designing processes. The incorporation of Kansei Engineering methodology into sound design practice in this study has demonstrated positive results from the users. The findings indicate Kansei Engineering as a viable method in the design of sound physical properties that could induce feelings and emotions.